Situation of plastic waste management and health conditions of people in Hai Duong coastal community of Thua Thien Hue province in 2020 - Ton, That Canh Tri; Nguyen, Van Thanh Nhan; Nguyen, Le Hanh Nguyen; Hoang, Thi Binh Minh; Nguyen, Dac Hoang Long; DangThi, Anh Thu (Tạp chí Y Dược Huế, 2022)
Background: Unmanaged plastic waste will affect the environment and human health. The study was conducted to describe the current situation of plastic waste management and the health conditions related to plastic waste of people in Hai Duong commune, Central Vietnam, in 2020. Methodology: A cross-sectional descriptive study using a structured questionnaire was carried out on 291 people over 18 years old in Hai Duong commune, Huong Tra town, from September to October, 2020. Results: The amount of plastic waste accounted for 16.5% of the total volume of collected waste. The main forms of plastic waste treatment included collecting at gathering places (87.3%), selling scrap (60.8%), or burning (19.9%). In most cases, plastic bags were collected at the gathering place (90.4%), washed for reuse (45.4%), and burned (14.8%). The notable weakness of garbage collection and transportation was that residents did not sort out different types of garbage (29.6%), and littered indiscriminately in public places with little traffic at night (11.3%). Health conditions related to over-plastic waste use included headache (9.6%), rash (4.8%), cardiovascular disease (5.2%), and gastrointestinal disease (3.4%). Conclusion: The management of plastic waste in general and plastic bags in particular is still inadequate. It could be seen that if a lot of plastic products were used and the waste was not handled properly, it would cause much harm to human health. Therefore, appropriate policies need to be implemented to improve local management of plastic waste as well as awareness and effective practices regarding garbage disposal.